Pengaruh Nilai-Nilai Ekonomi Islam Terhadap Perilaku Konsumen Muslim Di Banda Aceh - Wan Sri Mahriana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of Islamic economic values on the behavior of Muslim consumers in Banda Aceh. Islamic economic values include principles of halal, justice, balance, and social responsibility, which guide consumer decision-making. This study uses a quantitative approach with a survey design involving 100 randomly selected Muslim respondents in Banda Aceh. Data were collected through Likert-scale questionnaires and analyzed using simple linear regression to test the influence of Islamic economic values on consumer behavior. The results indicate that Islamic economic values have a positive and significant impact on Muslim consumer behavior, reflected in careful spending patterns, preference for halal products, avoidance of usury, and awareness of the social impact of consumption. These findings demonstrate that Islamic economic principles serve not only as moral guidance but also as practical determinants in everyday consumer decisions. This research has important implications for businesses to develop products and services in accordance with Islamic economic principles, as well as for government and related institutions in formulating policies that support an Islamic lifestyle and halal consumption. The study also provides opportunities for further research to explore other factors that may strengthen the influence of Islamic economic values on Muslim consumer behavior.